Austrian Video 1983 - 1986. - Insam, Grita (Wien : Galerie Grita Insam, 1986)
Bielz, Gudrun ; Schnell, Ruth ; Capellari, Wolfgang ; Sturminger, Christian ; Graf, Inge / ZYX ; Hintze, Ide ; Mark, Helmut ; Moser, Gertrude - Wagner ; Pas Paravant (Renate Kocer + Karl Kowanz) ; Putz, Rupert ; Rainer, Helmut ; Weibel, Peter ; Weigand, Hans ; Wiener, Zelko
Austrian Video 1983 - 1986, Galerie Grita Insam, Wien, 1986
Duits
kunstcatalogus
Keywords: Oostenrijk